DUAL-POEM for associated esophageal and gastric motility disorders: case series of endoscopic cardiomyotomy and endoscopic pyloromyotomy. (3rd May 2020) - Monino, Laurent; Gonzalez, Jean-Michel; Lestelle, Valentin; Vitton, Véronique; Barthet, Marc
Abstract: Background: Per-oral esophageal myotomy endoscopic (E-POEM) has clearly proved safety and efficiency in the treatment of esophageal spastic disorders. Recent studies on endoscopic pyloromyotomy (G-POEM) suggest good efficiency and safety in the treatment of gastroparesis. In recent literature, some reports showed both esophageal motility disorders and gastroparesis. Methods: We report the case of four patients with esophageal and gastric motility disorders who were successfully treated with DUAL POEM (E-POEM and G-POEM) in two separate procedures. Results: Clinical improvement was reported in all patients with a decrease of the Eckardt score for esophageal motility disorders and a decrease of the GCSI score for gastroparesis. No adverse events occurred after any procedure. These reported cases suggest that is possible to perform an E-POEM and a G-POEM in the same patient in two distinct procedures. Conclusions: DUAL POEM seems to be faisable in patient with esophageal motility disorders associated with gastroparesis. The possibility of the concomitant occurrence of esophageal and gastric motility disorders could lead to change in practices with an overall assessment including gastric empting scintigraphy, high resolution manometry and pH-impedancemetry for patients with digestive motility disorders.